Analysis of the Response of Transmission Line Network under Electromagnetic Pulse. Issue 2 (March 2021) - Wang, Xutong; Guo, Jinghai
Abstract: Power system transmission line is a very complex network. The response of cable terminal is very different from that of single line. In order to accurately predict the terminal response of the cable under the nuclear electromagnetic pulse, a convenient method is needed to calculate the response of complex network. Based on the state equation method and the extrapolation method, the transmission line is equivalent to the current source or voltage source. Matlab program and Simulink are used to calculate the induced current generated by the cable terminal. The results are compared with those of CST cable studio. The results of CST show that the method is correct.